13C‐Detected Through‐Bond Correlation Experiments for Protein Resonance Assignment by Ultra‐Fast MAS Solid‐State NMR. Issue 13 (15th April 2013) - Barbet‐Massin, Emeline; Pell, Andrew J.; Knight, Michael J.; Webber, Amy L.; Felli, Isabella C.; Pierattelli, Roberta; Emsley, Lyndon; Lesage, Anne; Pintacuda, Guido
Abstract We present two sequences which combine (1H, 15N) and (15N, 13C) selective cross‐polarization steps with an efficient variant of the J‐based homonuclear transfer scheme, in which a spin‐state‐selective (S3E) block is incorporated to improve both resolution and sensitivity in the direct 13C dimension. We propose these two sequences as a part of a suite of four N–C correlation experiments allowing for the assignment of protein backbone resonances in the solid state. We illustrate these experiments under ultra‐fast magic angle spinning conditions on two samples of microcrystalline dimeric human superoxide dismutase (SOD, 153×2 amino acids), in its diamagnetic ("empty", ZnII) and paramagnetic (CuII, ZnII) states.